1971
DOI: 10.1037/h0031646
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of human faces: Effects of target exposure time, target position, pose position, and type of photograph.

Abstract: Three experiments investigated Ss' ability to recognize a target person (whom they had previously seen) in a test series of ISO pictures of faces. The longer the original exposure to the target and the earlier the target picture appeared in the test series, the greater the probability of recognition. The pose position in the test series (front, profile, or portrait view) and the type of photograph (color or black and white) did not affect recognition. These results have implications for procedures used by law … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
105
2

Year Published

1985
1985
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(115 citation statements)
references
References 7 publications
8
105
2
Order By: Relevance
“…This may, at first, seem contradictory to the results of Hsiao and Cottrell (2008) who indicated that only the first two fixations were required. However, there is plenty of evidence that suggests that longer exposure times lead to more fixations and greater recognition accuracy (Bruce, 1982;Ellis, 1981;Laughery, Alexander, & Lane, 1971;Shepherd, Gibling, & Ellis, 1991). This is not due to a larger number of features being sampled (Coin & Tiberghien, 1997), but rather the most diagnostic features being encoded more effectively.…”
Section: Discussionmentioning
confidence: 99%
“…This may, at first, seem contradictory to the results of Hsiao and Cottrell (2008) who indicated that only the first two fixations were required. However, there is plenty of evidence that suggests that longer exposure times lead to more fixations and greater recognition accuracy (Bruce, 1982;Ellis, 1981;Laughery, Alexander, & Lane, 1971;Shepherd, Gibling, & Ellis, 1991). This is not due to a larger number of features being sampled (Coin & Tiberghien, 1997), but rather the most diagnostic features being encoded more effectively.…”
Section: Discussionmentioning
confidence: 99%
“…A high degree of variability between faces within a given set is found to enhance face recognition performance (Brown & Lloyd-Jones, 2006). Longer exposure time (Laughery, Alexander & Lane, 1971), and more elaborate encoding, such as categorizing faces according to their psychological properties (e.g., how honest is the person) in contrast to their physical properties (e.g., race categorization), have resulted in greater recognition accuracy (Bower & Karlin, 1974;Winograd, 1978). Classifying faces on the basis of their psychological properties is considered to entail more elaborative processing, resulting in more accurate recognition (Winograd, 1981).…”
Section: Face Recognitionmentioning
confidence: 99%
“…Zusne discovered from these patterns that the eye receives the most attention. Laughery et al [3] ascertained that users ranked facial features in the following order of importance: eyes; nose; mouth; lips=chin; hair; and finally the ears. The majority of facial perception studies support the theory that the face is the most viewed area of a head-shoulder image; furthermore, past studies have concluded that individuals are most likely to focus their attention on the areas around the eyes and the mouth.…”
Section: Discussionmentioning
confidence: 99%